If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9m+10=46
We move all terms to the left:
9m+10-(46)=0
We add all the numbers together, and all the variables
9m-36=0
We move all terms containing m to the left, all other terms to the right
9m=36
m=36/9
m=4
| -14+6=-2(x+6) | | 5=6(y-2)-1 | | 12m-27=7m+43 | | 17+4=-3(2x-7) | | 4x+1.4=6.2 | | 4x-17=-11 | | 9x-8=5x-10 | | 2.3=(t-1.8)/2 | | -6(n-6)=12 | | x/5+x/8=13/14 | | 4(2x+9)=-40+44 | | 3n+1=-6-4n | | 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 | | 6x+3=5x–20 | | 40=5(d-72) | | X+6÷3=2x÷4 | | -36=-6(f-78) | | 9(m−3)+3m=7m+43 | | -7=3+2/3x | | -5=x-1/5 | | -5(4x-4)=4(5-5x)+0 | | -4.68=u/6+3 | | 6(1+3m)=-8(5-2m)-4 | | X2+3x+1=4x+3 | | 3a+7a=-5+4a-1 | | 5(x-57)+15=15 | | 2/3(c-1)=2c+1/2 | | 1.1+w/7=-16.4 | | 9.8=6.1+-d | | 8(2y+6)5y=37 |